Palladium-Catalyzed Functionalization of Olefins and Alkynes: From Oxyalkynylation to Tethered Dynamic Kinetic Asymmetric Transformations (DYKAT) - Nicolai, Stefano; Orcel, Ugo; Muriel, Bastian; Greenwood, Phillip D. G.; Buzzetti, Luca; Puriņš, Mikus; Waser, Jerome (Synlett, 2020)
This review presents an account of the palladium-catalyzed functionalizations of alkenes and alkynes developed at the Laboratory of Catalysis and Organic Synthesis (LCSO). Starting from the intramolecular oxy- and aminoalkynylation of alkenes, tethered methods were then developed to functionalize allylic amines and alcohols, as well as propargylic amines. Finally, a new dynamic kinetic asymmetric transformation was developed based on the use of a ‘one-arm’ Trost-type ligand, giving access to enantiopure amino alcohols. Each section is a personal account by the researcher(s) who performed the work.1 Introduction,2 Oxy- and Aminoalkynylation of Olefins,3 In Situ Tethering Strategies for the Synthesis of Vicinal Amino Alcohols and Diamines,4 Carboamination of Allylic Alcohols,5 Carbooxygenation of Propargylic Amines,6 Enantioselective Carboetherification/Hydrogenation via a Catalytically Formed Chiral Auxiliary,7 Conclusion
Keywords: synthetic methods; palladium catalysis; alkynes; Trost ligands; DYKAT